THE ROLE OF KYAI'S LEADERSHIP IN PREPARING QUALITY SANTRI : (Case Study of Darussalam Gontor Modern Islamic Boarding School) - Yayat Suharya; Agustinah; Diyah Yuli Sugiarti (Jurnal Visipena, 2018)
Islamic boarding is the oldest educational institution in Indonesia which has a role in character education. The main purpose of this study was to understand the role of kyai's leadership in preparing quality santri. This paper aims at exploring the values which become the basis for leadership practice at Gontor. However, Gontor exists and gradually develops with its own unique management and leadership system. The study suggests that Gontor has its own standards which are mainly based on Islamic values. Indeed, there are a lot of values, but basically they can besimplified into the five spirits of Pondok Pesantren namely sincerity, simplicity, self reliance, Islamic brotherhood, and freedom. Each one of these spirits becomes a standard of excellence for Gontor leadership. In other words, Gontor will always exist, continue to flourish, create quality santri and prosper if it maintains these spirits and will deteriorate by the erosion of them.